Preventing school injuries : a comprehensive guide for school administrators, teachers, and staff - Posner, Marc. (New Brunswick, NJ : Rutgers University Press, 2000)
Offers school administrators, teachers, and staff a comprehensive overview of the best methods for injury prevention in school, and examines why so many students are injured while on school property.
Includes bibliographical references (p. [219]-234) and index.
Adult
Keywords: School accidents -- United States -- Prevention; School accidents -- Prevention